2021
DOI: 10.3389/fgene.2021.771062
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CBX Molecular Family in Lung Adenocarcinoma Tumorigenesis and Immune Infiltration

Abstract: Background: The members of the Chromobox (CBX) family are important epigenetic regulatory molecules with critical biological roles in many tumors. However, no study has analyzed or verified their role in lung adenocarcinoma (LUAD).Methods: UALCAN and Oncomine databases were used to analyze CBX expression in LUAD, and the cBioPortal database was used to analyze CBX genetic variations. The Kaplan-Meier plotter and UALCAN databases were used to identify molecules with prognostic value. Gene Ontology pathway, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Expression of CBXs in cancers. Compared with normal tissues or paracancerous tissues, the expression of all or some of the CBX1/2/3/4/5/8 members is upregulated in most cancer tissues, including glioma (67-69), tongue squamous cell carcinoma (TSCC) (70), head and neck squamous cell carcinoma (HNSCC) (71), breast cancer (BC) (15,(72)(73)(74)(75)(76)(77)(78)(79)(80), non-small cell lung cancer (NSCLC) (81)(82)(83)(84)(85), esophageal cancer (EC) (86)(87)(88)(89)(90), gastric cancer (GC) (91)(92)(93)(94)(95)(96)(97)(98), pancreatic adenocarcinoma (PAAD) (99,100), colorectal cancer (CRC) (101-104), urinary bladder cancer (UBC) (105), sarcoma (106) and osteosarcoma (107,108). As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell r...…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of CBXs in cancers. Compared with normal tissues or paracancerous tissues, the expression of all or some of the CBX1/2/3/4/5/8 members is upregulated in most cancer tissues, including glioma (67-69), tongue squamous cell carcinoma (TSCC) (70), head and neck squamous cell carcinoma (HNSCC) (71), breast cancer (BC) (15,(72)(73)(74)(75)(76)(77)(78)(79)(80), non-small cell lung cancer (NSCLC) (81)(82)(83)(84)(85), esophageal cancer (EC) (86)(87)(88)(89)(90), gastric cancer (GC) (91)(92)(93)(94)(95)(96)(97)(98), pancreatic adenocarcinoma (PAAD) (99,100), colorectal cancer (CRC) (101-104), urinary bladder cancer (UBC) (105), sarcoma (106) and osteosarcoma (107,108). As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell r...…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 99%
“…I, the expression of CBX3 is positively correlated with the tumor grade and/or stage of most cancer types, such as glioma and TSCC (70), lung adenocarcinoma (LUAD) (84), GC (91), HCC (116), CRC (101) and osteosarcoma (107), while the expression of CBX7 is negatively correlated with the tumor stage and grade of LUAD (84) and CCA (112). In addition, higher expression of CBX1/2/4/5/6/8 was associated with a higher tumor stage and grade in certain cancer types (11,67,69,74,76,80,84,86,90,99,104,108,111,118). Furthermore, higher expression of CBX3 was associated with a larger size of glioma (69) and osteosarcoma (107).…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed the distinct Integrative Analysis of Genetic and Epigenetic Alterations in the CBX7 Gene Reveals Oncol Insights.2023;2:691 functions among CBX family members in cancer. For example, CBX3 was found to be upregulated, whereas CBX7 was downregulated in many types of human cancer [14][15][16][17][18][19][20][21][22]. Some studies have shown that CBX3 transcriptionally suppresses the p21 gene to promote cell proliferation [23][24][25], while CBX7 transcriptionally suppresses CCNE1 expression to inhibit cell proliferation [26].…”
Section: Introductionmentioning
confidence: 99%